2021
DOI: 10.1108/er-10-2020-0477
|View full text |Cite
|
Sign up to set email alerts
|

Labour remuneration in the healthcare sector of Ukraine in terms of decent work concept

Abstract: PurposeHigh European standards of life quality are declared in a set of legislative documents in Ukraine, but the rewarding policy for the healthcare employees because of the coronavirus disease 2019 (COVID-19) disease remains not fully implemented. The purpose of the study is to develop indicators, standards and methods of assessing rewarding policies for healthcare employees in terms of providing decent labour remuneration that are useful for all stakeholders of the healthcare sector in Ukraine.Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The findings of Tsymbaliuk and Shkoda (2022) demonstrates how poorly the amount of the healthcare staff's decent pay corresponds to their performance. It has been shown that employee nursing personal and career progress and remuneration benefits are closely associated (Lee & Chui, 2019).…”
Section: Literature Review Theoretical Framework and Hypotheses Devel...mentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of Tsymbaliuk and Shkoda (2022) demonstrates how poorly the amount of the healthcare staff's decent pay corresponds to their performance. It has been shown that employee nursing personal and career progress and remuneration benefits are closely associated (Lee & Chui, 2019).…”
Section: Literature Review Theoretical Framework and Hypotheses Devel...mentioning
confidence: 99%
“…Hospitals have distinctive organisational structures and cultural environments within the healthcare industry and there are status differences between doctors and other healthcare workers including nurses, managers and professions related to medicine (Tsymbaliuk & Shkoda, 2022;Kamselem, Nuhu, & Liman, 2020;Lee, Lee, & Phan, 2020;Lee & Chui, 2019;Jonczyk & Buchelt, 2015;Currie et al, 2015). Nurses and geriatricians have combination middle manager positions within the interprofessional status and these hybrid middle managers have dual responsibilities for implementing management policies and clinical practices (Currie et al, 2015).…”
Section: Literature Review Theoretical Framework and Hypotheses Devel...mentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare institutions belong to the service sector, in which one of the key factors is the human capital factor. Accordingly, while analyzing their systemic innovation-and technology-driven development, sufficient attention should be paid to the presence and adherence to following the paradigm of personnel management of a healthcare institution [26], the quality and efficiency of the system of work motivation [27], the professional development of personnel [28], the level and structure of the system of remuneration and financial incentives for employees of healthcare institutions, especially in a part of experts and specialists [29].…”
mentioning
confidence: 99%